Expansion of Legal Measures Beyond Article 77 of The Criminal Code Concerning Pretrial and Constitutional Court Decision No. 76/PUU-XII/2014: Case Study No. 16/PDT. G/2022/PN. CBD - Yazdi, Ahmad; Ahmad, Sufmi Dasco; Satory, Agus (Civiliza Publishing, 2025)
This research discusses the expansion of legal remedies beyond Article 77 of the Indonesian Criminal Procedure Code (KUHAP) concerning pretrial mechanisms, focusing on the application of Constitutional Court Decision No. 76/PUU-XII/2014 in the context of civil tort claims (Perbuatan Melawan Hukum). The case study involves Case No. 16/Pdt.G/2022/PN.Cbd at the Cibadak District Court. Using a normative juridical and case study approach, the study analyzes primary legal documents, statutory regulations, and judicial decisions. Findings indicate that the investigator's summons without gubernatorial approval violated procedural legality and constitutional protection principles. Furthermore, premature media exposure of the plaintiff's identity contravened the presumption of innocence and caused immaterial harm not remediable through pretrial mechanisms. Thus, the tort lawsuit serves as a complementary alternative to pretrial review, reinforcing comprehensive legal protection for constitutional rights and personal reputation.